Predictors of Functional Outcome and Mortality in Endovascular Treatment for Acute Basilar Artery Occlusion: A Single-Centre Experience - Cao, Jie; Mo, Yi; Chen, Ronghua; Shao, Huaming; Xuan, Jinggang; Peng, Ya; Zhu, Xucheng (Frontiers in Neurology, 2021)
Background and Purpose: The objective of this study was to identify prognostic factors of endovascular treatment in patients with acute basilar artery occlusion and add evidence about the efficacy and safety of endovascular treatment for acute basilar artery occlusion. Materials and Methods: We reviewed the data of 101 patients with acute basilar artery occlusion receiving endovascular treatment from January 2013 to September 2019. Baseline characteristics and outcomes were evaluated. A favourable functional outcome was defined as a mRS of 0 to 2 assessed at the 3-month follow-up. The association of clinical and procedural characteristics with the functional outcome and mortality was assessed. Results: The study population consisted of 101 patients: 83 males and 18 females. Successful recanalization was achieved in 99 patients (97.1%). A favourable clinical outcome was observed in 50 patients (49.5%), and the overall mortality rate was 26.7%. A favourable outcome was significantly associated with NIHSS score at admission and lung infection . Mortality was associated with NIHSS score at admission, the number of thrombectomy device passes, the postoperative pons-midbrain index, and diabetes mellitus. Conclusions: This study suggested that NIHSS score at admission, the number of thrombectomy device passes, the postoperative pons-midbrain index, diabetes mellitus, and lung infection can predict the functional outcome and mortality. These initial results add evidence about the efficacy and safety of endovascular treatment for acute basilar artery occlusion and need to be confirmed by further prospective studies.